Psychometric properties of the General Self-efficacy Scale in Lima university students in times of health crisis - Anicama Gómez , José Carlos (2023)
The General Self-efficacy Scale has been used to evaluate various populations around the world, since this variable is important to develop alternative social behaviors to psychopathological ones. The objective: was to obtain the psychometric evidence of the General Self-efficacy Scale. Methodology: 1100 university students were evaluated with the Baessler and Schwarzer General Self-efficacy Scale modified by Anicama and Cirilo (2012). Results: A normal distribution and corrected item-test correlation coefficients greater than .30 were found. Adequate fit indices were identified for a one-dimensional model with item covariance (x2/df=4.465; GFI=.974; CFI=.973; TLI=.964; RMSEA=.056; SRMR=.0273; AIC=191.329). Likewise, inverse correlations were found with the Social Anxiety Questionnaire for adults (CASO) by Caballo et al. and with the Stress Scale for communicable diseases APA by Anicama et al. Cronbach's Alpha and McDonald's Omega had values greater than 0.70. Conclusions: This study reaffirms the validity and psychometric reliability of the General Self-efficacy Scale in a sample of university students from Lima.